Clinical practice of rapid antigen tests for SARS-CoV-2 Omicron variant: A single-center study in China - Chen, Mengyuan; Xu, Jiaqin; Ying, Lingjun; Cai, Miaoguo; Tung, Tao-Hsin; Zhou, Kai; Zheng, Yufen; Bi, Xiaojie; Wang, Jing; Tu, Xi; Shen, Bo; Lv, Dongqing (Virologica Sinica, 2022)
Responding to the fast-spreading SARS-CoV-2 Omicron variant, to improve screening efficiency, rapid antigen tests (RATs) were first added as a supplementary detection method in China in mid-March, 2022. What and how big a role RATs should play need to be supported by clinical data. Here, RAT performance and relevant factors in comparison with nucleic acid amplification tests (NAATs) were assessed in Omicron-infected inpatients. From the NAAT results, nasopharyngeal swabs (NPs) performed better than oropharyngeal swabs (OPs). RATs tested on NAAT positive NPs performed better than those with OP-positive samples. The RAT positivity rate was strongly associated with high levels of N and OFR1ab genes, especially in NPs where patients also had significantly longer hospital stays and shorter days from symptom onset to RAT testing. Self-performed RATs had a detection accuracy that was comparable to professionally performed RATs when the subjects were well guided. The antigen negative rate of the studied patients was 100% at discharge. These findings suggest that, in addition to a supplementary detection role, RATs can be an important strategy for evaluating the disease progression of Omicron-infected inpatients. This study provides important clinical data to support better rules regarding RATs under China's COVID-19 prevention and control policy. •Disease progression time and gene level in nasopharynx were relevant factors on RAT.•Accuracy rate of self-performed RATs was comparable to professionally-performed RAT.•RATs may be an important strategy for COVID-19 progression evaluation.